Increased Coal Slagging Index by Using Zeolite Synthetic - Idi Amin; Muh. Zulfikri Syahbar (SAGA: Journal of Technology and Information System, 2023)
The use of coal as fuel has experienced several obstacles, one of which is the formation of Slagging (crust). Slagging is formed by the melting point of coal ash or low ash fusion temperature, caused by low levels of Al2O3 in coal ash. The addition of synthetic zeolite to coal before use is intended to increase the level of Al2O3, so that it will increase  the ash fusion temperature  of coal ash. The  increase in ash fusion temperature also causes an increase in the slagging index of coal. With the high increase in  the slagging index obtained, the lower the potential for the formation of slagging. The smaller the potential  of Slagging formed, the use of coal also decreases. This study aims to determine the effect of adding waste-based synthetic zeolite to coal  ash on increasing coal slagging index. Research uses a type of experimental research. Itis collected by conducting laboratory tests, namely making observations and direct testing of samples with variations in the addition of synthetic zeolite to coal by 5%, 10%, and 15%. The results showed that synthetic zeolite added to coal was able to reduce the potential for slagging formation. Slagging index from the results of research for oxidation conditions is a standard sample of 1,246oC, SBZ5 by 1,242oC, SBZ10 by 1,250oC, and SBZ15 by 1,274oC. Reduction conditions i.e. standard sample of 1,130oC, SBZ5 by 1,116oC, SBZ10 by 1,136oC, and SBZ15 by 1,168oC. SBZ15 sample is a variation that has a  good slagging index, which is for oxidation conditions which is 1,274oC, and for reduction conditions that is 1,168oC